Twelve Tips for Better Communication with Patients During History-Taking - Aminur Rahman; Saria Tasnim (The Scientific World Journal)
Eliciting proper history from a patient is of paramount importance to establish an accurate diagnosis and management in medical practice. Good communication skill is a prerequisite for an effective physician patient relationship. A systematic search of medical literature has been made to formulate a guideline for better communication during history taking. The guideline emphasizes on both physical environment and emotional encounter and the key points are expressed as tips on relevant issues.